Value Alignment and Public Perceived Legitimacy of the European Union and the Court of Justice - Grosfeld, Eva; Scheepers, Daan; Cuyvers, Armin (Frontiers in Psychology, 2022)
The present study aims to extend research on the role of values for the perceived legitimacy of legal authorities by focusing on (1) supranational legal authorities and (2) a broad range of values. We examine how (alignment between) people’s personal values and their perception of the values of the European Union (EU) are related to perceived legitimacy of the Court of Justice of the EU (CJEU) and the EU more broadly. Inspired by moral foundations theory, we distinguish between individualizing (i.e., “democracy”, “liberty”, “fairness”) and binding values (i.e., “rule of law”, “respect for national authority”, “respect for tradition”). An online survey was conducted in six EU member states (N = 1136). A factor analysis confirmed a two-factor model (individualizing vs. binding values) for both personal values and perceived EU values. Four regression models were run for each of the value factors, including personal values, perceived EU values, and their interaction, on each of the outcomes (i.e., perceived CJEU and EU legitimacy). Perceived endorsement by the EU of both individualizing and binding values predicted higher legitimacy perceptions of the CJEU and EU. Furthermore, personal binding values had a negative effect on perceived EU legitimacy when participants perceived the EU to weakly support binding values, but a positive effect when the EU was perceived to strongly support binding values. The results suggest that value alignment plays an important role in perceived legitimacy of the CJEU and EU, and that better representing binding values might be a strategy to improve perceived EU legitimacy.